Distribution and abundance of marine mammals in the coastal waters of British Columbia, Canada - Williams, Rob; Thomas, Len (J. Cetacean Res. Manage., 2023)
Information on animal distribution and abundance is integral to wildlife conservation and management. However abundance estimates have not been available for many cetacean species inhabiting the coastal waters of Canada’s Pacific coast, including those species that were heavily depleted by commercial whaling. Systematic sightings surveys were conducted in the inshore coastal waters of the Inside Passage, between the British Columbia (BC)-Washington and the BC-Alaska borders. A total of 4,400km (2,400 n.miles) of trackline were surveyed in the summers of 2004 and 2005. Abundance estimates (with 95% confidence intervals) assuming certain trackline detection for seven cetacean species were as follows: harbour porpoise, 9,120 (4,210-19,760); Dall’s porpoise, 4,910 (2,700-8,940); Pacific white-sided dolphin, 25,900 (12,900-52,100); humpback whale, 1,310 (755-2,280); fin whale, 496 (201-1,220); common minke whale, 388 (222-680); and ‘northern resident’ killer whale, 161 (45-574). The potential for responsive movement to have affected the accuracy and precision of these estimates is difficult to assess in small-boat surveys. However, the analyses were designed to minimise this factor in the most obvious case (Pacific white-sided dolphins) and pilot data collection has begun to assess the magnitude of the effect and to calculate correction factors for other species. The density of harbour seals, both along the shoreline and at sea, was calculated and it was estimated that total abundance of harbour seals in the study area was at least 19,400 (14,900-25,200). These are new abundance estimates for this region for all cetacean species except killer whales. The small sample size makes the killer whale estimate tenuous, but one worth noting, as it is close to the known number of northern resident killer whales (2004 census was 219 animals, Cetacean Research Program, Pacific Biological Station, Fisheries and Oceans Canada). The common minke whale abundance estimate is similarly tentative, however the results do reveal that common minke whales were relatively rare in this region. While the majority of harbour seals were found as expected in the southern straits and in the mainland inlets, a substantial number of animals were on the north coast and in the Queen Charlotte Basin as well. These data provide a systematic snapshot of summertime distribution and abundance of marine mammals in the Queen Charlotte Basin, where offshore oil and gas development and seismic surveys for geophysical research have been proposed to take place. Similarly, the abundance estimates could be used to form the basis of a simulation exercise to assess the sustainability of observed levels of incidental bycatch of small cetaceans in commercial fisheries. The results described here provide a useful reference point to which future survey data can be compared.